Succession Analysis of Gut Microbiota Structure of Participants from Long-Lived Families in Hechi, Guangxi, China - Minhong Ren; He Li; Zhen Fu; Quanyang Li (Microorganisms, 2021)
The gut microbiota structure has been proposed to be involved in longevity. In this study, trajectories of age-related changes in gut microbiota were analyzed by comparing the gut microbiota composition from long-lived families. A specific bacterial community pattern and signature taxa of long-lived people were found in long-lived families, such as the enrichment of Enterobacteriaceae in all age groups and the higher abundances of Christensenellaceae, Verrucomicrobiaceae, Porphyromonadaceae, Rikenellaceae, Mogibacteriaceae, and Odoribacteraceae in long-lived elderly and the positive correlation between them. The cumulative abundance of the core microbiota was approximately stable along with age, but the genera and species in the core microbiota were rearranged with age, especially in Ruminococcaceae and Lachnospiraceae. Compared with the control group, the proportions of Lachnospiraceae, Roseburia, and Blautia were significantly higher in participants from the long-lived village, but their abundances gradually decreased along with age. Based on functional predictions, the proportions of pathways related to short-chain fatty acid metabolism, amino acid metabolism, and lipoic acid metabolism were significantly higher in the long-lived elderly compared with the offspring group. The trajectory of gut microbiota composition along with age in participants from long-lived families might reveal potential health-promoting metabolic characteristics, which could play an important role in healthy aging.